2011
DOI: 10.1164/rccm.201009-1409oc
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Promotes Fibroproliferative Acute Respiratory Distress Syndrome by Inhibiting Peroxisome Proliferator–activated Receptor-γ

Abstract: Leptin signaling is required for bleomycin-induced lung fibrosis. Leptin augments TGF-β(1) signaling in lung fibroblasts by inhibiting PPARγ. These findings provide a mechanism for the observed protection against ARDS observed in diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
89
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 66 publications
(79 reference statements)
2
89
0
Order By: Relevance
“…Previous reports have also shown that leptin and leptin receptor are expressed in airway epithelium (24), and bronchial expression of leptin is increased in chronic obstructive pulmonary disease (25,26). Leptin seems to be involved in embryonic lung growth and maturation (27,28), and in fibroproliferative responses in the lung to bleomycin (29). Furthermore, polymorphisms in leptin and leptin receptor have been associated with differences in lung function (30,31).…”
Section: Discussionmentioning
confidence: 94%
“…Previous reports have also shown that leptin and leptin receptor are expressed in airway epithelium (24), and bronchial expression of leptin is increased in chronic obstructive pulmonary disease (25,26). Leptin seems to be involved in embryonic lung growth and maturation (27,28), and in fibroproliferative responses in the lung to bleomycin (29). Furthermore, polymorphisms in leptin and leptin receptor have been associated with differences in lung function (30,31).…”
Section: Discussionmentioning
confidence: 94%
“…Bellmeyer and coworkers (13) found that exogenously administered leptin causes ALI in mice and that leptin resistance protects mice from hyperoxia-induced lung injury. Jain and coworkers (12) showed that leptin levels in bronchoalveolar lavage fluid are increased in patients with ALI, and that leptin promotes fibroproliferative ALI by increasing transforming growth factor-b1 transcription in a peroxisome proliferator-activated receptor-g-dependent fashion (12), suggesting that leptin may not only promote ALI, but may contribute to lung fibrosis in response to injury, possibly shedding light on a mechanistic link between PGD and small airways fibrosis (obliterative bronchiolitis) after lung transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that obesity is a novel risk factor for ALI among the critically ill (9,10), perhaps by altering the milieu of proinflammatory and antiinflammatory cytokines produced by adipose tissue (so-called "adipokines") (11)(12)(13), such as leptin and adiponectin. Leptin in particular has been shown to play a role in the development of ALI in a hyperoxia mouse model and to contribute to the fibroproliferative stage of the acute respiratory distress syndrome (12,13).…”
mentioning
confidence: 99%
“…Shore and coworkers have previously shown that leptin infusion increases airway reactivity in lean mice; this is not related to increases in allergic airway inflammation, suggesting that leptin may be having effects in pathways quite distinct from those involved in allergic asthma (16). The observation that leptin was inversely related to lung function as measured by FEV 1 is also intriguing, given reports that leptin is involved in lung development (17,18) and may regulate fibroproliferative responses in the lung (19). Further studies evaluating the mechanistic relevance of elevated TNFa and leptin in airway disease in obese individuals with asthma are needed.…”
mentioning
confidence: 99%